Pattern and characterization of headache among adult patients visiting the neurology clinic in Benin City Nigeria - Odiase FE; kayode-Iyasere EO (Ibom Medical Journal, 2020)
Context: Headache is one of the commonest reasons for neurology clinic consultation worldwide, but there is a dearth of knowledge regarding the pattern and characteristics of headache in parts of the southern region of Nigeria. Objectives: This study aims to describe the pattern and characteristics of headaches among adult patients attending a neurology clinic. Material and Methods: This was a cross-sectional study, done at the neurology clinic, Central Hospital Benin City. Adults with headache complaints were consecutively recruited using a structured questionnaire. Demographics of participants, headache characteristics, investigations and treatment were captured, while SPSS version 21 was used for data analysis Results: During the 7-month study period (February to September 2018), three hundred and sixty-eight patients attended the neurology clinic, of which one hundred and ten were recruited (29.9%, 110/368). The mean age of participants was 52.0(16.5) yrs. Headache was commoner in the female (69.1%) than the male (30.9%) participants. About half of the patients had 1-5 episodes of headaches in the previous six months, with majority of them attributing stress (47.3%), noise (31.8%), fatigue (28.2%) and lack of sleep (20.0%) as the main triggers of their headache. Reduced work productivity was observed in 52% of respondents, while 50.2% of participants self-treated themselves with the majority (64.5%), of them taking acetaminophen for their headache Conclusion: There is the need for a greater public awareness on headache to stem the self-treatment behavior that was observed, which would enable a more holistic care of the headache condition.